Product Recall: An Evaluation of Few Issues - Vijayalakshmi, N. K.; Madegowda, J. (Indian Journal of Marketing, 2012)
Right from the beginning of the new millennium, many corporate giants have proven that the recall of their products from the market was inevitable. In spite of the technological advancements, the consumers are put into a dilemma about the safety of the products they use. However, the product liability laws of the countries protect the consumers from defective and/or dangerous products by holding manufacturers and distributors responsible for putting them into the market place. This paper looks into different issues pertaining to reverse logistics mechanism, which proves that the burden of product recall is transferred ultimately to the consumers who cannot free themselves from the shackles of the deprivation of the assured quality from the manufacturers and distributors. At the same time, this paper throws light on the pressure on the manufacturers and distributors created by the copycat complaints of the consumers which forces them to recall their products from the market, which cannot be ignored.